2022
DOI: 10.1186/s13098-022-00899-6
|View full text |Cite
|
Sign up to set email alerts
|

Masked nocturnal hypertension as a result of high prevalence of non-dippers among apparently well-controlled hypertensive patients with type 2 diabetes mellitus: data from a prospective study

Abstract: Background: Ambulatory blood pressure monitoring (ABPM) in patients with diabetes mellitus (DM) and hypertension (HTN) show the dipping patterns, identify masked uncontrolled hypertension (MUCH), and demonstrate the effectiveness of the blood pressure (BP) treatment. MUCH is associated with a two-fold higher risk of adverse events. Prevalence in patients with DM is between 13.3 and 66.4%. Our study aims to investigate the prevalence of MUCH and the BP patterns in a population of apparently well-controlled hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A further point should be made. MH may present different clinical patterns such as persistent out-of-office hypertension, isolated daytime, or isolated nocturnal hypertension [ 49 ]. Information on this issue, based on four of the studies included in the meta-analysis, revealed that MH patients (identified according to daytime BP criteria) had significantly higher nocturnal BP values than controls.…”
Section: Discussionmentioning
confidence: 99%
“…A further point should be made. MH may present different clinical patterns such as persistent out-of-office hypertension, isolated daytime, or isolated nocturnal hypertension [ 49 ]. Information on this issue, based on four of the studies included in the meta-analysis, revealed that MH patients (identified according to daytime BP criteria) had significantly higher nocturnal BP values than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Short BP phenomena (morning BP peaks, BP variability and morning BP surge) have been shown to adversely affect the incidence of cardiovascular outcomes independent of 24-h mean BP values. Night-time BP has been identified as a more important predictor of cardiovascular events and mortality than daytime BP, and several studies have shown that an attenuation of the physiological nocturnal BP fall (non-dipping) [167][168][169], a nocturnal BP rise (reverse dipping) [170,171] or even an isolated nocturnal hypertension [172,173] are more common than previously thought. However, these notions cannot be translated into management recommendations because no randomized clinical trial has been carried out to demonstrate additional cardiovascular benefits of focusing treatment on the correction of a raised nocturnal BP, an excessive BP variability or a marked BP increase at arousal.…”
Section: Other Blood Pressure Measurement Modalitiesmentioning
confidence: 99%
“…Using ambulatory blood pressure monitoring with a Holter device, we can identify the non-dipping or reverse-dipping blood pressure profiles. A decrease in blood pressure from day to night of <10% identifies non-dipping and, respectively, reverse dipping [ 14 ]. Nondipping is more common in diabetic patients (39-62%) than in the general population, while reverse dipping is present in 9-30%.…”
Section: Introductionmentioning
confidence: 99%